Low-caffeine green tea supplementation reduced lithium serum levels and the relative abundance of microbiota in women with obesity: A case study - Natália Yumi Noronha; Guilherme da Silva Rodrigues; Vanessa Fernandes Rodrigues; Carolina Ferreira Nicoletti; Luzânia dos Santos Martins; Luísa Maria Diani; Heitor Bernardes Pereira Delfino; Marcela Augusta de Souza Pinhel; Lígia Moriguchi Watanabe; Wellington Tavares de Sousa Júnior; Déborah Araújo Morais; Fernando Barbosa Júnior; et al. (Clinical Nutrition Open Science)
Summary: Background: Green tea (GT) polyphenols play an important and known role in the oxidative and inflammatory response due to their antioxidant, anti-inflammatory, anti-hyperglycemic, and anti-obesity properties. However, its relation to the detoxification of toxic metals and its possible effect remains unknown. Purpose: The present study investigated the relationship between GT intake, toxic metals detoxification, and gut microbiota in obesity. Methods: Each participant in the group initially received 56 capsules of low-caffeine GT from the Solaray® brand. After four weeks of supplementation, another 56 capsules were given, totaling 112. All assessments were performed pre- and post-GT intervention. Serum metal levels were determined using an inductively coupled plasma mass spectrometer (PerkinElmer, NexION 2000 B, Waltham, MA, EUA, EUA). Fecal DNA was extracted using the QIAmp® Fast DNA Stool MiniKit (QIAGEN). Results: Intervention with GT did not promote changes in the clinical or metabolic data evaluated. However, GT supplementation led to a significant decrease of 48% in Lithium concentration in the post-intervention period compared to the pre-intervention period. This study also observes the prebiotic effect of green tea in modulating Bacteroidetes and Firmicutes. Conclusions: The GT effect of Lithium reduction is a new finding in the literature. There is a lack of investigation to address the effects of the components of the GT in lithium excretion, and we attribute this effect to the trace amount of caffeine.